2014
DOI: 10.1007/s00284-014-0687-4
|View full text |Cite
|
Sign up to set email alerts
|

GABA Accumulation in Response to Different Nitrogenous Compounds in Unicellular Cyanobacterium Synechocystis sp. PCC 6803

Abstract: GABA accumulation and glutamate decarboxylase (GAD) activity, the principal enzyme involved in GABA formation, was investigated in cyanobacterium Synechocystis sp. PCC 6803 wild-type (WT) and gad knockout mutant strains grown in medium containing different nitrogenous compounds. Nitrate was the best nitrogen source for GAD activity and GABA accumulation followed by nitrite, ammonium, and urea. An increase in the accumulation of GABA was observed in WT and mutant cells grown for 24 h in medium supplemented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Carbon source and nitrogen source are two essential components for the growth and metabolism of microorganisms. They were proven to induce the expression of some enzymes [29,30] and supposed, in this case, to affect the biotransformation ability of C. sinensis . Hence, we chose some carbon sources and nitrogen sources to investigate their influences on the biotransformation of ginsenoside Rb1.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon source and nitrogen source are two essential components for the growth and metabolism of microorganisms. They were proven to induce the expression of some enzymes [29,30] and supposed, in this case, to affect the biotransformation ability of C. sinensis . Hence, we chose some carbon sources and nitrogen sources to investigate their influences on the biotransformation of ginsenoside Rb1.…”
Section: Resultsmentioning
confidence: 99%
“…Glutamate was not yet described as compatible solute in cyanobacteria (Klähn and Hagemann 2011) and might act as small storage compound because of the decreased glutamate level at night in all strains. A higher glutamate decarboxylase activity and GABA accumulation was observed for Synechocystis with the addition of glutamate to the medium (Kanwal et al. 2015).…”
Section: Discussionmentioning
confidence: 99%
“…PCC 6803 was obtained from the Pasteur culture collection. The Δ gdc mutant was constructed previously 14 by deleting the gdc gene ( sll1641 ) in the WT Synechocystis . Approximately 5% (v/v) of a 14-d-old cell culture was inoculated into BG-11 medium 15 without citrate but supplemented with 20 mM HEPES-NaOH (pH 7.5).…”
Section: Methodsmentioning
confidence: 99%
“…We found that gdc inactivation reduced the metabolites levels in the TCA cycle, but increased the accumulation levels of PHB and pyruvate. Since, gdc inactivation has also been shown to significantly increase the glutamate (Glu) level in Synechocystis 14 , we next asked whether the increased PHB level mediated by gdc inactivation was a consequence from the increased Glu level or from the affected TCA cycle. To address this, a section of the metabolic network that links Glu metabolism, the TCA cycle and PHB synthesis was examined by analyzing relevant metabolites and enzymatic activities.…”
Section: Introductionmentioning
confidence: 99%